The Influence of Viral Marketing, Product Quality, and Price on Consumers’ Purchase Intention for Converse Shoes in Sidoarjo City (Among Generation Z TikTok Users in Sidoarjo) - Indah Nillam Kurnia; Lilik Indayani (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the influence of viral marketing, product quality, and price on purchase intention toward Converse shoes among Generation Z TikTok users in Sidoarjo. This topic is important because digital platforms, particularly TikTok and affiliate-based promotion, have accelerated the spread of product information and shaped young consumers’ purchasing behavior in the fashion industry. A quantitative survey method was employed using a structured questionnaire. The population consisted of 128 Generation Z consumers in Sidoarjo who showed interest in buying Converse shoes, and the Slovin formula with a 5% error tolerance resulted in a sample of 96 respondents selected through simple random sampling. Data were analyzed using SPSS 26, including validity and reliability tests, classical assumption tests, and multiple linear regression. The results indicate that viral marketing has a positive and significant effect on purchase intention (t = 3.621; p < 0.05), product quality also has a positive and significant effect (t = 2.494; p < 0.05), and price shows the strongest positive and significant effect (t = 5.858; p < 0.05). Simultaneously, the three variables significantly influence purchase intention (F = 105.924; p < 0.05). The coefficient of determination (R²) is 0.775, indicating that 77.5% of the variance in purchase intention can be explained by viral marketing, product quality, and price, while the remaining 22.5% is influenced by other factors not examined in this study. This study reinforces the viral marketing–product quality–price framework in explaining purchase intention among Generation Z TikTok users. In conclusion, viral marketing, product quality, and price significantly affect purchase intention for Converse shoes in Sidoarjo, with price as the most dominant factor.